Las capacidades físicas y su incidencia en la danza y baile contemporáneo en la sección de danza de la Universidad Nacional de Loja - Soto Jiménez, Darwin Manuel (2015)
This research entitled "PHYSICAL SKILLS AND ITS IMPACT ON THE CONTEMPORARY DANCE DANCE DANCE IN THE SECTION OF THE NATIONAL UNIVERSITY OF LOJA, raise the question how physical abilities are influencing the contemporary dance performances and dance section Dance of the National University of Loja !, the goal is to understand how they affect the physical abilities in presentations of dance and contemporary dance in the dance section of the National University of Loja by resorting to scientific review in deepening the topics; Dance, Contemporary Dance, physical and character using methods deductive, inductive, analytic and synthetic to investigate the problem for the fulfillment of the objectives capacities survey techniques were used mainly. The universe of this thesis consisted of thirty dancers, with an average age of 16. Section Dance of the National University of Loja, it was determined the following results that most of the dancers feel the need for a fitness program, concluding that the lack of a physical training program does not allow for development of physical abilities, which affects the presentation of dance groups, contemporary dance Dance section of the National University Loja, leading to the problem, suggesting consider my proposal called "fitness program for dancers of the Dance section of the National University of Loja" as part of vocational training.